Jaden Scott: capstone - Scott, Jaden, artist (Colorado State University. Libraries, 2023)
The artist's statement: Memories are invaluable to me. They are passed from person to person, generation to generation, friend to friend, and will outlive what they remember. Sharing these memories through storytelling, artifacts, hidden meanings, and manifested abstract ideas are the goals of my work. Being able to show a deeply personal experience from the inside and share it outwardly is at the root of my expression of memories. I create to hold onto family, friends, past and future versions of myself, and my own challenges I faced in small physical fragments. My work is a collection of personal souvenirs. My personal souvenirs are all rooted in narratives: being diagnosed with an incurable disease, past and future versions of myself, my background in dance, my exploration of gender, and, most prominently: my heritage. My grandparents were farmers and lived on a multi-acre farm, their work ethic and overall way of life heavily inspire my work and the narratives I tell. It is important for me to take these experiences and transform them into work, through which I take the time to reflect on them and myself during the process. In my fibers practices, I focus on bringing together materials, techniques, and physicality that have a lot of importance to me and the work. The larger acts of movement that go into these pieces feed energy into the work. I sit with the pieces and self reflect on myself and the work during the long hours of the process. I find that quilting and weaving allow me the most opportunity for this through physicality and movement. In those techniques, I use a lot of hand-dyed and found materials that feed into the overall depth of meaning in my works. I find satisfaction in the intense physical labor and time spent needed to produce my fibers works. By creating work that dives into deeply personal stories, I am able to dissect the impacts certain events had on me and process them through my work. Taking multiple hours to go through the process of creating a piece allows me time to sit with the ideas and events, and come out the other side a little bit wiser. There is a lot of nuance in the choices I make during my process and I can spend hours detailing the entire story and reasoning in each piece I make. It is my goal to share my narratives, my love for the craft, and myself through my works.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers